ANTIFERTILITY ACTIVITY OF DECASCHISTIA CROTONIFOLIA LEAF EXTRACT ON MALE RATS - SHAIK, AFSAR; RAJU YALAVARTHI, PRASANNA; BONNOTH, CHANDRASEKHAR KOTHAPALLI (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: The objective was to investigate the male antifertility effect of Decaschistia crotonifolia leaf extract on male Wistar rats. Methods: The animals were divided into three groups of five animals each. The first group (I) served as control and received normal saline, and remaining Groups II and III were treated with plant extract at a dose of 200 and 400 mg/kg p.o., respectively, for 21 days. Results: Dose-dependent significant decrease in the weight of testes and epididymis was observed. Furthermore, a dose-related reduction in sperm count and motility was observed. A significant decrease in testosterone levels leading to infertility was also observed. Conclusion: The 70% methanolic leaf extract of D. crotonifolia has produced dose-dependent antifertility effect on male rats.